The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.2337/db07-1444
|View full text |Cite
|
Sign up to set email alerts
|

Direct Administration of Insulin Into Skeletal Muscle Reveals That the Transport of Insulin Across the Capillary Endothelium Limits the Time Course of Insulin to Activate Glucose Disposal

Abstract: OBJECTIVE-Intravenous insulin infusion rapidly increases plasma insulin, yet glucose disposal occurs at a much slower rate. This delay in insulin's action may be related to the protracted time for insulin to traverse the capillary endothelium. An increased delay may be associated with the development of insulin resistance. The purpose of the present study was to investigate whether bypassing the transendothelial insulin transport step and injecting insulin directly into the interstitial space would moderate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
80
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(94 citation statements)
references
References 56 publications
(46 reference statements)
10
80
3
Order By: Relevance
“…After local delivery of insulin to the skin, an increase in interstitial lactate and pyruvate was measured within the first 15 minutes, although the interstitial glucose concentration was not significantly changed. This is in contrast with previous studies, in which insulin was administered to muscle and a glucose decrease was observed (Chiu et al, 2008;Rosdahl et al, 2000). One explanation to why we did not observe a decrease in glucose in the skin, could be a rapid glucose supply from to the vasculature to the tissue, that may have been facilitated by insulin-mediated vasodilation.…”
Section: Microvascular and Metabolic Actions Of Insulin In The Skincontrasting
confidence: 55%
“…After local delivery of insulin to the skin, an increase in interstitial lactate and pyruvate was measured within the first 15 minutes, although the interstitial glucose concentration was not significantly changed. This is in contrast with previous studies, in which insulin was administered to muscle and a glucose decrease was observed (Chiu et al, 2008;Rosdahl et al, 2000). One explanation to why we did not observe a decrease in glucose in the skin, could be a rapid glucose supply from to the vasculature to the tissue, that may have been facilitated by insulin-mediated vasodilation.…”
Section: Microvascular and Metabolic Actions Of Insulin In The Skincontrasting
confidence: 55%
“…However, this human study did not report actual levels of interstitial insulin but instead reported change from basal. Access to muscle is a major component of insulin sensitivity (1,11) likely due to the microvascular effects of insulin, which increase distribution of blood through muscle, thus increasing delivery to the insulin-sensitive tissues.…”
mentioning
confidence: 99%
“…TET transport of insulin is the rate limiting step in time pharmacokinetic profile of insulin [9].This was observed in experiments utilizing glucose clamp technique. There was a time delay between achieving steady state insulin concentration in the plasma and thoracic duct lymph collections while the gradient between plasma and interstitial fluid insulin concentrations remained constant.…”
Section: Transendothelial Transport As the Rate Limiting Stepmentioning
confidence: 93%